Inﬂuence of boron content on electrochemical properties of boron-doped diamond electrodes and their utilization for leucovorin determination. - Šelešovská, Renáta; Kränková, Barbora; Štěpánková, Michaela; Kelíšková, Pavlína; Janíková, Lenka; Chýlková, Jaromíra; Vojs, Marian (My University, 2018)
Set of the lab-made boron-doped diamond electrodes (BDDEs) prepared with various B/C ratio (1000, 2000, 4000, 8000, 10,000, and 20,000 ppm) in the gas phase was subjected to the detailed characterization in the present paper. It was proved, that the B/C ratio inﬂuenced the electrochemical features of the working electrodes like a width of the potential window, which decreased with increasing B/C. Variations of reversibility of two redox systems (Fe(CN)63−/4− and Ru(NH3)62+/3+) depending on B/C were observed as well. The best electrochemical properties were found for BDDE with B/C 10000 ppm. Moreover, the working electrodes were tested for voltammetric analysis of leucovorin based on its oxidation. The lab-made BDDEs were applied for voltammetric analysis of the pharmaceutical preparation containing leucovorin with excellent results (recovery 97.7–103.3%, RSD5 ≤ 2.1%).
Vliv obsahu boru na elektrochemické vlastnosti borem dopovaných diamantových elektrod a jejich využití pro stanovení leukovorinu.
Keywords: Voltammetry; Boron-doped diamond electrode; Boron content; Leucovorin; Pharmaceutical samples; Voltametrie; Borem dopovaná diamantová elektroda; Obsah boru; Leukovorin; Farmaceutické vzorky